Digital Education in Indonesia: Implementation of Telkomsel's CSR Program Through the Lombok Cluster Skul.id Application - Luluk Fadliyanti; Meilia Giana Putri; Baiq Saripta Wijimulawiani; Ida Ayu Putri Suprapti; Vici Handalusia Husni; Jaka Anggara (Pascasarjana Universitas Mataram, 2025)
Digital education plays a crucial role in the modern era, along with the rapid advancement of technology and the need for digital competencies in various sectors. In Lombok, educational challenges include limited internet access, lack of online learning infrastructure, low quality and competence of teachers in the use of digital media, and lack of continuous training. To answer these problems, Telkomsel initiated the Corporate Social Responsibility (CSR) program through the Skul.id application with the main goal of improving access and quality of digital education, as well as empowering teachers and students on the island of Lombok. The method of implementing community service includes intensive training for teachers on the use of Skul.id platforms, technical and pedagogical assistance, provision of hardware and connectivity, and periodic monitoring and evaluation to ensure sustainability. It is hoped that this program can improve students' literacy and digital skills, improve teachers' teaching methods, and create a learning ecosystem that is inclusive and adaptive to technological developments. Potential impacts include increasing learning motivation, equitable distribution of educational opportunities, and strengthening collaboration between schools, communities, and the digital industry. The success of this program is also expected to be a replication model for similar initiatives in other regions of Indonesia.